A GLUTAMATE CYSTEINE LIGASE gene StGSH1 regulated by StERF10 enhanced glutathione accumulation and adaptation to low phosphorus stress in potato - Tian, Xiaocheng; Li, Mingjun; Huang, Xiaojia; Wirtz, Markus; Zheng, Xiaohui; Fan, Shilong; Tian, Jiang; Liu, Shaoqun; Liu, Zhonghua; Zhao, Hongbo (Advanced science, 2025)
Potato (Solanum tuberosum L.) is a staple global food crop whose growth is constrained by soil phosphorus deficiency. While glutathione (GSH) modulates abiotic stress responses, its precise function and regulation in potato adaptation to low-phosphorus (LP) remains undefined. This study demonstrated that LP triggers GSH accumulation by up-regulating GLUTAMATE-CYSTEINE LIGASE (StGSH1), the rate-limiting enzyme in GSH biosynthesis. Pharmacological inhibition using buthionine sulfoximine (BSO) and exogenous GSH supplementation confirmed the essential role of GSH in LP adaptation. Confocal microscopy showed that StGSH1-GFP fusions localize to plastids in potato protoplasts. Overexpression and silencing of StGSH1 demonstrated that it maintained reactive oxygen species (ROS) homeostasis and attenuated LP-induced damage. StGSH1 also coordinated membrane lipid remodeling by upregulating both phospholipid catabolic genes (StNPC/PLD) and sulfolipid anabolic genes (StSQD1/2), shifting lipid flux from phosphatidylethanolamine (PE) to sulfoquinovosyldiacylglycerol (SQDG). Additionally, ETHYLENE RESPONSE FACTOR 10 (StERF10) is identified as a direct transcriptional activator of StGSH1. BSO-mediated GSH depletion reduced the LP adaptation in StERF10-OE plants, whereas GSH supplementation rescued StERF10-RNAi plants, indicating StERF10 conferred LP adaptation largely through StGSH1-mediated GSH biosynthesis. Collectively, these findings establish the StERF10-StGSH1 module as a critical nexus connecting GSH biosynthesis to LP adaptation, providing a rational target for breeding varieties with enhanced phosphorus use efficiency.